SELF-DEVELOPMENT IN THE EDUCATIONAL PROCESS TRANSFORM THEORY INTO IDEAS AND TECHNOLOGIES ADVANTAGES OF ADAPTATION (Conferencea, 2025)
This thesis examines the role of current educators in organizing the modern educational process. Self-development to apply innovative ideas and technologies. The theoretical aspects of improvement are revealed and through this, students' knowledge is improved. A comprehensive idea about the methods and ways to take higher education to a new level. Also, currently, modern methods are used in the educational process ways to improve traditional teaching methods, traditional teaching methods. The theoretical basis for harmonizing with new modernization methods passed.